Factors affecting early detection of cervical cancer: a scoping review - Fitri Ayu Marpal; Ismarwati Ismarwati (International Journal of Health Science and Technology, 2023)
Cervical cancer is still one of the most common cancers in women, with a total of 604,127 new cases of cervical cancer, where the death rate reached 341,831 in 2020. The achievement of early detection of cervical cancer in 2016 was 1.5 million or 3.5% of women, while the government's target was 50% of women to do early detection of cervical cancer. This review aims to determine the factors that influence the early detection of cervical cancer. The scoping review method uses the PRISMA-ScR checklist mapping. Article selection using PRISMA Flowchart with stages carried out starting from identifying article searches, filtering articles based on titles and abstracts, selecting articles based on full text, critical appraisal, and article results used. The databases used are PubMed, Wiley, and Science Direct. There were 11 relevant articles out of 713 were found based on inclusion and exclusion criteria, depicted in 3 themes: predisposing factors, supporting factors, and driving factors, including age, knowledge, education level, distance affordability, access to information, family support, and health workers. The implementation of early detection of cervical cancer is still very low in developing countries, so there needs to be a good understanding of awareness and knowledge about cervical cancer and its screening among women in developing countries.